2008
DOI: 10.1075/ml.3.2.06sch
|View full text |Cite
|
Sign up to set email alerts
|

Language switching in bilingual speech production

Abstract: Recent research on language production suggests that bilinguals shift from using inhibitory control mechanisms to a language-specific selective mechanism during development (Costa, Santesteban, & Ivanova, 2006). Costa et al. argue that the robustness of the L2 lexical representations may be critical to the functionality of a language-specific selective mechanism. Accordingly, in the present study we measured the lexical robustness of a group of 54 English dominant learners of Spanish using a verbal fluency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
102
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(118 citation statements)
references
References 0 publications
13
102
0
Order By: Relevance
“…This finding is in line with Filippi et al (2014), who found that asymmetrical switch costs were negatively correlated with L2 proficiency in a word naming task, and Schwieter and Sunderman (2008), who found that switch costs get symmetrical at a certain L2 proficiency threshold (measured by verbal fluency). These studies indicate the importance of language proficiency in language switching and more specifically with regard to asymmetrical switch costs.…”
Section: Highly Proficient Bilinguals Vs Second Language Learnerssupporting
confidence: 79%
See 3 more Smart Citations
“…This finding is in line with Filippi et al (2014), who found that asymmetrical switch costs were negatively correlated with L2 proficiency in a word naming task, and Schwieter and Sunderman (2008), who found that switch costs get symmetrical at a certain L2 proficiency threshold (measured by verbal fluency). These studies indicate the importance of language proficiency in language switching and more specifically with regard to asymmetrical switch costs.…”
Section: Highly Proficient Bilinguals Vs Second Language Learnerssupporting
confidence: 79%
“…These findings led to acknowledge that some inhibition might be required during bilingual language production of highly proficient bilinguals. Yet, this was only the case in very distinct contexts (see also Schwieter & Sunderman, 2008).…”
Section: Highly Proficient Bilinguals Vs Second Language Learnersmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies demonstrate how two (or more) mental lexicons may be stimulated at one time within different processes of language processing. The process of inhibitory control (a process which effectively blocks a non-target language, theorized to occur at less proficient levels of language use -see Schwieter & Sunderman, 2008;Schwieter & Sunderman, 2011;Schwieter, 2013), and language-specific mechanisms models (Schwieter & Sunderman, 2008) have been explored, but research is nowhere near conclusive in this area (Finkbeiner, Almeida, Janssen & Caramazza, 2006). While results are not completely consistent, cognates have served as a useful tool for investigating cross-linguistic influence, and considerable headway has been made in this area of linguistics.…”
Section: Cognate Effectmentioning
confidence: 99%